GROWTH AND NUTRITIONAL STATE OF SCHOOLCHILDREN OF THE CENTER OF SPORT AND LEISURE SANTA ETELVINA - NORTH AREA OF MANAUS. (Fiep Bulletin - online, 2013)
This research has the objective of analyzing the growth and children's nutritional state and adolescents, in the age group from seven to 14 years, of both sexes, of Santa Etelvina's CEL. This study is characterized as a descriptive research, where the measures anthropometrics body weight and stature will be collected, using the procedure described by Ferreira (2005). The evaluation of the nutritional state will be accomplished by the criteria of Waterlow (1976), being used as reference pattern the model of National Center it goes Health and Statistics (NCHS) and the classification of Waterlow, recommended by the World Health Organization (WHO, 1995). The data will be submitted to the program of Evaluation and Nutritional State in Pediatrics (PED). The sample is constituted of 265 school, being 87 female and 178 male. The results show that regarding the growth, for both sexes the values are below the patterns of reference of NCHS and of the Program of Family budget (POF), and as for the state nutritional, same most being classified as eutrophic, there is still a very big prevalence of malnutrition, and these school ones are distributed as undernourished chronic, undernourished past and undernourished current. They were found few cases of overweight and obesity, demonstrating that, it is with the problem of the malnutrition that we should worry, therefore this can cart serious problems for the child, committing his/her physical and cognitive development.
Keywords: growth; nutritional state; malnutrition